Does inflammation mediate the association between obesity and hearing status in mid-childhood and mid-life? - Wang, Jing; Liy, Mengjiao; Sung, Valerie; Grobler, Anneke; Saffery, Richard; Lange, Katherine; Burgner, David; Wake, Melissa (My University, 2022)
Obesity is characterized by heightened inflammation, and both phenotypes are associated with hearing loss. We aimed to determine if inflammation mediates the associations between obesity and hearing ability in mid-childhood and mid-life. Participants: 1165 11- to 12-year-old children and 1316 parents in the population-based cross-sectional Child Health CheckPoint within the Longitudinal Study of Australian Children. Adiposity measures: Body mass index (BMI) classified as normal, overweight and obesity; waist-to-height ratio (WHtR) classified as <0.5 and ≥0.5; fat mass index. Inflammatory biomarkers: Serum glycoprotein A (GlycA); high-sensitivity C-reactive protein (hsCRP). Audiometry: Composite high Fletcher Index (mean threshold of 1, 2, 4 kHz) in the better ear. Causal mediation analysis decomposed a 'total effect' (obesity on hearing status) into 'indirect' effect via a mediator (eg GlycA, hsCRP) and 'direct' effect via other pathways, adjusting for age, sex and socioeconomic position. Compared to adults with BMI within the normal range, those with obesity had hearing thresholds 1.9 dB HL (95% CI 1.0-2.8) higher on the high Fletcher Index; 40% of the total effect was mediated via GlycA (indirect effect: 0.8 dB HL, 95% CI 0.1-1.4). Children with obesity had hearing thresholds 1.3 dB HL (95% CI 0.2-2.5) higher than those with normal BMI, of which 67% (indirect effect: 0.9 dB HL, 95% CI 0.4-1.4) was mediated via GlycA. Similar mediation effects were noted using other adiposity measures. Similar but less marked mediation effects were observed when hsCRP was used as the inflammatory biomarker (6-23% in adults and 23-33% in children). Inflammation may play an important mediating role in the modest hearing reductions associated with obesity, particularly in children. These findings offer insights into possible mechanisms and early prevention strategies for hearing loss.
International Journal of Obesity
Keywords: Health and wellbeing